2014
DOI: 10.3126/jcmsn.v9i2.9686
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Minimal Invasive Percutaneous Plate Osteosynthesis in closed fractures of distal tibia

Abstract: Background Treatment of fracture distal tibia is challenging. Classic open reduction and internal plate fixation requires extensive soft tissue dissection and causes periosteal injury. The locking screw-plate interface allows fracture fixation without plate-bone adherence, thus preserving the fracture hematoma, and reduces the risk of nonunion by maintaining microvascular circulation within the cortex and its investing tissues. Material & Methods This study included 33 patients of age between 18 to 62 years wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…The periosteum is not disturbed, and being a closed procedure, there is no disturbance of the fracture hematoma, thereby having less risk of infection. 28,30 by 78.72. % (37 cases) vs. 21.27% (10 cases) with boy to girl ratio of 3.7:1.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The periosteum is not disturbed, and being a closed procedure, there is no disturbance of the fracture hematoma, thereby having less risk of infection. 28,30 by 78.72. % (37 cases) vs. 21.27% (10 cases) with boy to girl ratio of 3.7:1.…”
Section: Discussionmentioning
confidence: 97%
“…12 Another study in Nepal by Mishra et al reported excellent results in 80 % and good results in the remaining 20% with no poor results. 28 Fracture geometry and location are essential determinants for surgical outcomes. In our study, TENS gave excellent results in transverse and short oblique fractures.…”
Section: Discussionmentioning
confidence: 99%
“…The clinico-radiological union rates at 12 weeks were 82.5 % for HI group and 90 % for P group. Previous study has shown average healing time to be 12-15 weeks in P. 23,25 While some studies have shown average union time in P to be 19 weeks and for HI to be 21 weeks. 20 Previous studies have reported satisfactory union rates when using the external fixation strategy as a definitive method of treatment in cases of tibial plafond fractures.…”
Section: Discussionmentioning
confidence: 97%